Tissue Sodium Concentration Quantification at 7.0-T MRI as an Early Marker for Chemotherapy Response in Breast Cancer: A Feasibility Study - Zaric, Olgica; Farr, Alex; Minarikova, Lenka; Lachner, Sebastian; Asseryanis, Ella; Nagel, Armin Michael; Weber, Michael; Singer, Christian F.; Trattnig, Siegfried (Radiology, 2021)
Background Tissue sodium concentration (TSC) is elevated in breast cancer and can determine chemotherapy response. Purpose To test the feasibility of using a sodium 23 (23Na) MRI protocol at 7.0 T for TSC quantification to predict early treatment outcomes of neoadjuvant chemotherapy in breast cancer and to determine whether those quantitative values provide additional information about efficacy. Materials and Methods Women with primary breast cancer were included in this prospective study. From July 2017 to June 2018, participants underwent 7.0-T 23Na MRI. Multichannel data sets were acquired with a density-adapted, three-dimensional radial projection reconstruction pulse sequence. Two-dimensional tumor size and TSC were evaluated before and after the first and second chemotherapy cycle, and statistical tests were performed based on the presence or absence of a pathologic complete response (pCR). Results Fifteen women with breast cancer and six healthy women were enrolled. The mean baseline tumor size in women with a pCR was 7.0 cm2 ± 5.0 (standard deviation), and the mean baseline tumor size in women without a pCR was 19.0 cm2 ± 12.0. After the first chemotherapy cycle, women with a pCR showed a reduced tumor size of 32.9% (2.3 cm2/7.0 cm2), compared with 15.3% (2.9 cm2/19.0 cm2) in those without a pCR. The areas under the receiver operating characteristic curve for tumor size reduction after the first and second chemotherapy cycle were 0.73 (95% CI: 0.09, 0.50; P = .12) and 0.93 (95% CI: 0.04, 0.60; P < .001), respectively. Women with a pCR had a mean baseline TSC of 69.4 mmol/L ± 6.1, with a reduction of 12.0% (8.3 mmol/L), whereas those without a pCR had a mean baseline TSC of 71.7 mmol/L ± 5.7, with a reduction of 4.7% (3.4 mmol/L) after the first cycle. The areas under the receiver operating characteristic curve for TSC after the first and second cycles were 0.96 (95% CI: 0.86, 1.00; P < .001) and 1.000 (95% CI: 1.00, P < .001), respectively. Conclusion Using 7.0-T MRI for tissue sodium concentration quantification to predict early treatment outcomes of neoadjuvant chemotherapy in breast cancer is feasible, with reduced tissue sodium concentration indicative of cancer response. © RSNA, 2021 Online supplemental material is available for this article.
CRIS-Team Scopus Importer:2021-04-09